Profile of Lung Cancer: A One-Year Report (Journal of Medicine, 2011)
Background: Lung cancer has been the most common cancer in the world since 1985 and the leading cause of cancer death. Worldwide it is by far the most common cancer of men and increasingly being recognized in Bangladesh. Objective: To observe the profile of lung cancer patients and the outcome of chemotherapy. Method: In one year (1st January’08 to 31st December’08) the lung cancer patients who attended the dept. of Medical Oncology were included in this study. The patient’s history, clinical evaluation, previous treatment record (surgical intervention, chemotherapy and radiotherapy), histopathology and other investigation reports were documented. Chemotherapy and or supportive and symptomatic treatment carried out in the department were noted and response of the treatment were observed and documented. Result: Total number of patients was 701.Of them, 608 males and 93 females; male female ratio: 6.53:1. Common occurrence (> 85%) at and above 50 years of old; age range 25 years to 95 years and mean age 62 years; 44% was illiterate and 40% had primary school education; more than 82% belonged to poor and bellow average socioeconomic status. Previous records showed 524 patients (about 75%) attended after diagnosis and 177 cases (25%) had had prior treatment (6 by surgery, 22 by radiotherapy and 147 by chemotherapy). On clinical evaluation, almost all patients were symptomatic with WHO Grade-2 (44.51%) and Grade -3 (26.68%) performance status. Right lung was affected more (55%). Pathologically non-small cell carcinoma was 81.45% and small cell carcinoma 18.55%. But histopathology differed by sex; squamous cell carcinoma (43.42%) was most common in male but in female it was adenocarcinoma (55.92%). All most all cases were at inoperable stage (locally advanced/metastatic cancer/ medically unfit). Thirty percent of male patients and 45% of females dropped out after first and second visit. Around 20% patients got only supportive symptomatic management in both sexes and 326 patients (296 male and 30 female) were treated by chemotherapy. Within three to six months of treatment, 10% of the patients showed complete symptomatic relief, weight gaining and radiological disappearance of tumor and all most all patients benefited of some sorts of symptoms relief. Conclusion: The lung cancer patients were at inoperable stages with WHO Grade 2 and Grade 3 performance status in most of the cases; needed much more supportive and symptomatic treatment. Chemotherapy was effective; complete clinical and radiological response in 10% of cases and others got benefit with some sorts of symptoms relief and radiological improvement. Keyword: Lung cancer, Bangladesh, squamous cell carcinoma, adenocarcinoma metastatic cancer, Chemotherapy, Bangladesh. DOI: http://dx.doi.org/10.3329/jom.v12i2.8417 JOM 2011; 12(2): 115-119